2021
DOI: 10.1590/1518-8345.4901.3467
|View full text |Cite
|
Sign up to set email alerts
|

Public-private relationship in surgical hospitalizations through the Unified Health System

Abstract: Objective: to characterize surgical hospitalizations, length of stay, cost and mortality, according to the legal nature (public and private) of the hospital institution linked to the Unified Health System (Sistema Único de Saúde, SUS). Method: a descriptive study, of the survey type, with retrospective data collection (2008 to 2017) and a quantitative approach. The dependent variables surgical hospitalizations in Brazil, costs, length of stay and mortality and the independent variables regime/legal nature (pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Specifically, the proportion of outpatients in member public hospitals decreased after the reform, whereas in member private hospitals, it was mainly the proportion of inpatients that declined. Previous studies have also shown that the proportion of hospitalizations in public hospitals is generally higher than that of private hospitals, and most of them were complex cases or operations required to treat patients with multiple injuries [ 17 19 ]. On the one hand, due to the different functional positioning of inpatient services and outpatient services, it is more difficult to treat diseases that require hospitalization and the level of medical services varies greatly among different medical institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the proportion of outpatients in member public hospitals decreased after the reform, whereas in member private hospitals, it was mainly the proportion of inpatients that declined. Previous studies have also shown that the proportion of hospitalizations in public hospitals is generally higher than that of private hospitals, and most of them were complex cases or operations required to treat patients with multiple injuries [ 17 19 ]. On the one hand, due to the different functional positioning of inpatient services and outpatient services, it is more difficult to treat diseases that require hospitalization and the level of medical services varies greatly among different medical institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned seals, in many services, the decisive factor for changes in the care process and in the degree of interventions performed ( 13 ) . This means that the service management method leads to the quality of care offered to people ( 22 ) . Thus, existence of a risk in this process, which can be, for example, signaled by the logic of the New Public Management, cannot be denied.…”
Section: Discussionmentioning
confidence: 99%
“…8 Data from Australia and the USA demonstrate a high degree of variation in length of stay (LOS), rates of transfer to inpatient rehabilitation following hip and knee arthroplasty, 9 and specific to private hospitals, higher unplanned stay (>2 hours) in recovery after surgery. 8 Considering the increasing number of elective surgeries and associated hospitalisations undertaken in private hospitals in Australia 10 and elsewhere, [11][12][13] reducing unwarranted clinical variation in these settings is critical to generating higher value care, improving patient outcomes, and reducing healthcare expenditure.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%